Estimating HIV incidence in the Akwa Ibom AIDS indicator survey (AKAIS), Nigeria using the limiting antigen avidity recency assay - Negedu-Momoh, O.R.; Balogun, O.; Torpey, K.; et al. (Journal of the International AIDS Society, 2021)
Introduction: HIV incidence estimates are important to characterize the status of an epidemic, identify locations and popula tions at high risk and to guide and evaluate HIV prevention interventions. We used the limiting antigen avidity assay (LAg) as part of a recent infection testing algorithm to estimate HIV incidence in the Akwa Ibom AIDS Indicator Survey (AKAIS), Nige ria. Methods: In 2017, AKAIS, a cross-sectional population-based study was conducted at the household (HH) level in 31 local government areas (LGAs) of Akwa Ibom state. Of the 8963 participants aged ≥15 years who were administered question naires for demographic and behavioural data, 8306 consented to HIV rapid testing. Whole-blood specimens were collected from 394 preliminary HIV-seropositive individuals for CD4+ cell count determination and plasma storage. Samples were shipped to a central quality laboratory for HIV confirmatory testing and viral load determination. A total of 370 HIV-positive specimens were tested for the recent HIV infection using the LAg assay. Results: Of the 8306 consenting adults, the HIV prevalence was 4.8%. Of the 370 HIV-positive samples tested for HIV recency, the median age was 35 years, 48.8% had CD4+ cell count >500/mm3 and 81.3% was not virally suppressed. Viral suppression was greater among females (21%) than for males (13%). A total of 11 specimens were classified as recent based on the LAg assay and HIV viral load ≥1000 copies/mL. The weighted, adjusted HIV-1 incidence was 0.41/100 person-years (95% CI 0.16 to 0.66); translating to 13,000 new cases of HIV infections annually in Akwa Ibom, a state with a population of 5.5 million. The HIV incidence rate was similar in females and males (0.41% and 0.42% respectively). The incidence rate was the highest among participants aged 15 to 49 years (0.44%, 95% CI 0.15 to 0.74) translating to 11,000 new infections annu ally, about 85% of all new infections in the state. Conclusions: The finding of the high HIV incidence among the 15 to 49-year age group calls for renewed and innovative efforts to prevent HIV infection among young adults in Akwa Ibom state.
Research Article
Keywords: HIV-1; incidence; recent infection; limiting antigen avidity; viral load; Nigeria